From threat to response: Cybersecurity evolution in Albania - Klorenta PASHAJ; Vilma TOMÇO; Eralda GJIKA (Smart Cities and Regional Development Journal)
As Albania's digital landscape expands, its vulnerability to sophisticated cyber threats increases correspondingly. This study explores the evolution of Albania's cybersecurity strategies, tracing the shift from reactive measures to a proactive defence approach. It critically examines significant cyber incidents that have shaped the national cybersecurity landscape, assessing how these have influenced the development of Albania's current cyber defence strategies. The focus is on how Albania has tailored its strategic responses to enhance digital resilience and national security. In the second part, the paper provides an in-depth review of the threat models prevalent in the Western Balkans and Albania, highlighting key areas where Albania's cyber management requires further development. One key recommendation is the forecasting of cyber-attacks, which could benefit from the application of time-series and machine learning techniques to enhance predictive capabilities. This approach emphasizes the importance of adapting to emerging threats and fostering international cooperation to bolster Albania's cybersecurity infrastructure.